Peran Perilaku Kerja Berbasis Praktek Manajemen Sumber Daya Manusia Islami Menuju Peningkatan Kinerja Organisasi - Sandy Mulya Adhi; Olivia Fachrunnisa (Jurnal Manajemen dan Bisnis Indonesia, 2017)
Human resource management practice and policy are indicated as one business strategy to improve organizational performance. Research on the linkage between HRM practices and organizational performance has been widely discussed, however, some of them show inconsistent results. Therefore, this study proposes employee work behavior as an intermediary to deliver the impact of HRM practices and policies with organizational performance. In particular, this article discusses HRM practices and policies on companies which provide service on spiritual activities, so that the HRM practices and policies are actualized on the basis of the organization values. This research aims to analyze the influence of Islamic Human Resources Management (HRM) Practices and Policies toward Islamic Work Behavior and Organizational Performance. 67 companies with their main business are organizing Hajj and Umrah involved in this research. Research result shows that respondens has been practicing HRM based on Islamic principles. There are positive and significant result on the influence of Islamic HRM Practices toward Islamic Work behavior, however, two practices namely selection and performance appraisal shows non significant result. This is due to the lack focus of companies in doing selection and performance appraisal. They might more focus on how to provide good service to the customers. Managerial implication and suggestion for future research are also discussed. Keywords: Islamic based HRM practices, HRM policies, Islamic work behavior, organizational performance